The Impact of Commercial Marketing on Developing Tour Guide Skills-A Survey Study of a Sample of Tourism and Travel Companies in Baghdad (Czech Journal of Multidisciplinary Innovations, 2025)
This study seeks to explore how commercial marketing contributes to enhancing the capabilities of tourist guides and examines the extent to which marketing criteria can be utilized to improve guide performance within the research community. The core research question focuses on whether commercial marketing can be strategically activated within tourism companies through long-term planning. To address this, the researcher analyzed responses from 215 distributed questionnaires targeting managers of tourism and travel companies in Baghdad. The study investigates the connection and influence between commercial marketing—viewed as the independent variable—and the development of tour guide skills as the dependent variable. A set of primary and secondary hypotheses was developed to guide the analysis. To meet the research objectives, which include directing tourism companies to recognize the added value brought by tour guides, a descriptive and analytical methodology was employed. Data collection primarily involved questionnaires and personal interviews, supported by various statistical techniques. The findings highlight that tourism and travel companies actively apply commercial marketing strategies to enhance their tour guides' performance by envisioning long-term growth and forming strategic alliances.